Highly Tunable and Degradable Hydrophobized Nanogels for the Intranasal Delivery of Poorly-Water Soluble Antipsychotic Drugs to the Brain - Simpson, Madeline J. (My University, 2020)
Nanogels are soft, deformable networks of cross-linked polymer swollen in water. Nanogels have the unique ability to swell in response to external physiological conditions. Their stimuli-responsive nature affects degradability, drug uptake and release, which can be exploited to create tunable drug delivery systems. The ability to alter the composition and structure of nanogels imparts advantageous characteristics for targeted drug delivery applications. Antipsychotic drugs (APDs) used to treat schizophrenia, a chronic neuropsychiatric disorder, are typically hydrophobic. Prolonged dosing causes neurological and metabolic side effects due to the systemic administration of drug. Patient adherence to APD administration is low, causing complications that contribute to the substantial burden of disease. APDs would benefit from nanogel encapsulation through improved solubility and controlled release kinetics to reduce the adverse side effects associated with typical administration protocols. This thesis presents the development of hydrophobized, biodegradable poly(oligoethylene glycol methacrylate) (POEGMA)-based nanogels to deliver APDs to the brain. Both an adaptation of conventional precipitation polymerization as well as a spontaneous self-assembly technique are utilized to synthesize nanogels containing different hydrophobic domains. Incorporation of cross-linkers with different modalities of biodegradability enable stimuli-responsive degradation and drug release. The effects on nanogel swelling, biodegradability, and APD uptake and release kinetics are explored in vitro. The preclinical application of these APD-loaded nanogels is evaluated using the minimally invasive intranasal (IN) route for delivery. We show that these nanogel delivery systems have therapeutic effects in terms of significantly altering a range of rodent behaviours, including locomotion inhibition, the onset of catalepsy, and improvement in pre-pulse inhibition, over extended periods of time in relation to current administration strategies. These drug-loaded nanogel delivery systems show potential to minimize the effective therapeutic dose by enhancing APD bioavailability via IN administration, thus reducing adverse outcomes and improving potential patient adherence to APD-based therapies in clinical use.
Keywords: Nanogel; Drug Delivery; Intranasal; Antipsychotic Drugs